Glycobiology of immune responses - Rabinovich, Gabriel Adrián (2012)
Unlike their protein roommates and their nucleic acid cousins, carbohydrates remain an enigmatic arm of biology. The central reason for the difficulty in fully understanding how carbohydrate structure and biological function are tied is the non-template nature of their synthesis and the resulting heterogeneity. While this Annals of the NYAS issue does not claim to hold all of the answers, the goal is to highlight what is known about how carbohydrates and their binding partners, on the microbial (non-self), tumor (altered-self) and host (self) sides, cooperate within the immune system while identifying areas of great opportunity to those willing to take up the challenge. In the end, these reviews will serve as specific examples of how carbohydrates are as integral to biology as proteins, nucleic acids, and lipids. In this introductory article we attempt to summarize general concepts on glycans and glycan-binding proteins (mainly C-type lectins, siglecs and galectins) and their contribution to the biology of the immune responses in physiologic and pathologic settings.